The Effect of Cooperative Learning Model Type Think Pair Share (TPS) on Student Learning Outcomes - Nurlaika, Fikra; Sahade, S.; Rijal, Abdul (Manunggal Halim Jaya, 2024)
This study aims to examine the effect of the Think Pair Share (TPS) Cooperative Learning Model on the learning outcomes of Class X students in the Accounting Expertise program at SMK Negeri 1 Gowa. The research employs an experimental design with a posttest-only control group, involving two groups: an experimental group utilizing the TPS model and a control group receiving conventional instruction. The sample consists of 68 students, divided equally between the two groups, selected through purposive sampling. Data collection techniques include observation, documentation, and tests, while data analysis is performed using SPSS 27.0 for Windows, encompassing descriptive statistics, validity tests, and hypothesis testing. The findings indicate that the TPS Cooperative Learning Model was implemented effectively, with a high average score of 91.2% in the experimental group. Descriptive analysis reveals that the learning outcomes in the experimental group averaged 86.24, significantly higher than the control group’s average of 61.76. Regression analysis shows a significant positive effect of the TPS model on learning outcomes, with a regression equation of Y' = 40.312 + 0.499X and a determination coefficient of 44.1%, indicating that the TPS model accounts for 44.1% of the variance in learning outcomes. The t-test results confirm that the TPS model significantly enhances learning outcomes (p < 0.05). These results align with previous studies and support the theoretical framework that cooperative learning models, particularly TPS, enhance student engagement and academic performance.